CompTIA security+ SY0-201 video course. - Harris, Shon; Miller, David, 1959 November 5- (Pearson Certification, 2009)
Systems Security Shon Harris The fast, powerful way to prepare for your CompTIA Security+ exam! Get all the hands-on training you need to pass (ISC)²'s tough SSCP exam, get certified, and move forward in your IT security career! In this online video, the world's #1 information security trainer walks you through every skill and concept you'll need to master. This online video contains over three hours of training adapted from Shon Harris's legendary five-day SSCP boot camps-including realistic labs, scenarios, case studies, and animations designed to build and test your knowledge in real-world settings! Comprehensive coverage of CompTIA Security+ domains of knowledge: . Blended Malware . How to Buffer Overflow Works . Identity Theft . Buffer Overflow . Hardware Security . Personal Firewall About the Shon Harris Security Series This online video is part of a complete library of books, online services, and videos designed to help security professionals enhance their skills and prepare for their certification exams. Every product in this series reflects Shon Harris's unsurpassed experience in teaching IT security professionals. Category: Security System Requirements OPERATING SYSTEM: Windows 2000, XP, or Vista; Mac OS X 10.4 (Tiger) or later MULTIMEDIA: DVD drive; 1024 x 768 or higher display; sound card with speakers COMPUTER: 500MHz or higher CPU; 128MB RAM or more.